Capturing change: a multiple single-case experimental design evaluating Forensic Outpatient Systemic Therapy for juvenile antisocial behavior - van Cappellen, S. Marjolein; Creemers, Hanneke E.; Hoogsteder, Larissa; Asscher, Jessica J. (Elsevier Ltd, 2026)
Background: Forensic Outpatient Systemic Therapy (FAST) was developed to address limitations of existing systemic and multimodal interventions for juvenile antisocial behavior, underscoring the need for a more fine-grained understanding of how and when individual change occurs during and after treatment. Therefore, change and underlying processes during and after FAST were examined in juvenile aggression, caregiver responsiveness, and juvenile-caregiver conflict. Methods: A multiple Single Case Experimental Design (SCED) with a multi-informant ABC design (A = baseline, B = treatment, C = follow-up) was conducted. Primary data included repeated measurements from nine juveniles (66.7% boys, Mage = 14.9 years, Mrecidivism risk = medium–high to high) and 15 caregivers (20% fathers) across 12 families. Change during (AB) and after treatment (AC) was analyzed visually and statistically. Results: Across all three outcome measures, positive change during treatment was demonstrated for four to five (of twelve) families and after treatment for three to four (of six) families. All but one participant demonstrated positive change during treatment and, where available, after treatment. Results frequently differed between family members, particularly for negative change, which − with one exception − was limited to a single outcome that varied across participants. Change patterns fluctuated, with several improvements emerging after treatment. Conclusions: Most families demonstrated positive change during and after FAST, although change varied across families and individuals. Multi-informant assessment is essential for accurately evaluating treatment. Therapists and families should be aware that change is gradual and fluctuating rather than linear, and that gains can consolidate or emerge post-treatment.
Keywords: Aggression; Antisocial behavior; Conflict; Forensic Outpatient Systemic Therapy (FAST); Intervention evaluation; Responsiveness; Single-case experimental design; Education; Developmental and Educational Psychology; Sociology and Political Science